Caecal volvulus: a rare entity of intestinal obstruction: 2 cases report - Talreja, Deep P.; Chawla, Rajesh K.; Haque, Parwez W.; Albatanony, Ayman A. (International Surgery Journal, 2022)
Caecal volvulus is a very rare cause of intestinal obstruction. Patients with this condition may present with variable clinical presentation ranging from intermittent, self-limiting abdominal pain to acute abdominal pain associated with progressive intestinal ischemia, sepsis, and death. In this report, we presented two cases of caecal twist which was diagnosed with series of radiological imaging and labs. The first patient, 83 years old male underwent caecopexy, appendicectomy, and the second female who was 36 years old underwent right hemicolectomy with ileocolic anastomosis. We reported our experience in the management of 2 cases of caecal volvulus in our department.